Sympathetic and Vagal Nerve Activity in COPD: Pathophysiology, Presumed Determinants and Underappreciated Therapeutic Potential - Spiesshoefer, Jens; Regmi, Binaya; Ottaviani, Matteo Maria; Kahles, Florian; Giannoni, Alberto; Borrelli, Chiara; Passino, Claudio; Macefield, Vaughan; Dreher, Michael (Frontiers in Physiology, 2022)
GRAPHICAL ABSTRACT